Cross-Sectional versus Longitudinal Survey Research: Concepts, Findings, and Guidelines - Rindfleisch, Aric; Malter, Alan J.; Ganesan, Shankar; Moorman, Christine (Journal of Marketing Research, 2008)
Marketing academics and practitioners frequently employ cross-sectional surveys. In recent years, editors, reviewers, and authors have expressed increasing concern about the validity of this approach. These validity concerns center on reducing common method variance bias and enhancing causal inferences. Longitudinal data collection is commonly offered as a solution to these problems. In this article, the authors conceptually examine the role of longitudinal surveys in addressing these validity concerns. Then, they provide an illustrative comparison of the validity of cross-sectional versus longitudinal surveys using two data sets and a Monte Carlo simulation. The conceptualization and findings suggest that under certain conditions, the results from cross-sectional data exhibit validity comparable to the results obtained from longitudinal data. This article concludes by offering a set of guidelines to assist researchers in deciding whether to employ a longitudinal survey approach.